Rwanda : Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2008)
Rwanda's second Poverty Reduction Strategy Paper, the Economic Development and Poverty Reduction Strategy (EDPRS), builds on the strong achievements in human capital development and promotes three flagship areas to mobilize resources and improve policy implementation and coordination across sectors. There has been rapid growth in the non-farm paid employment sector. Executive Directors support the EDPRS to provide an adequate framework for poverty reduction in Rwanda. The immediate risks to growth and poverty reduction are shocks related to regional conflict and unpredictable weather patterns.